2019
DOI: 10.2478/ssa-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

Sorption properties of granulometric fractions in Haplic Cambisol developed from boulder loam

Abstract: The aim of the paper was to investigate the sorption properties of granulometric fractions separated from the genetic horizons of arable Haplic Cambisol developed from boulder loams of the Middle-Polish (Riss) Glaciation, Wartanian Stadial (central Poland). Separation of granulometric fractions was made with application of the Atterberg method without the use of centrifuging and dispersing agents. The cation exchange capacity average value in cmol(+)kg−1 and % contribution in particular fractions reached: 1–0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…10B, particularly in subhorizon Ap1 increased from 85% in the soil of the 0NPK variant to 87.2% in 2NPK. This may have been caused by partial extraction of calcium from carbonates during assays of basic cations (Brogowski and Chojnicki, 2019). Those authors extensively described the role of calcium in the modification of CEC in arable soils developing from glacial tills.…”
Section: Resultsmentioning
confidence: 99%
“…10B, particularly in subhorizon Ap1 increased from 85% in the soil of the 0NPK variant to 87.2% in 2NPK. This may have been caused by partial extraction of calcium from carbonates during assays of basic cations (Brogowski and Chojnicki, 2019). Those authors extensively described the role of calcium in the modification of CEC in arable soils developing from glacial tills.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the formation of soil organic and inorganic complex can promote the formation of soil aggregates, make soil become soft without agglomeration, and change the physical and chemical properties of soil. In addition, the physical migration of organic and inorganic complex in soil causes the redistribution of soil materials, affecting the adsorption of metals on soil particles of different particle sizes [31][32][33]. However, previous studies on the effects of soil components on mercury biogeochemical behavior were mainly conducted from the perspective of individual components, with little attention paid to the interactions among several individuals factors of various components [34][35][36][37][38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%